Characterization of RF receiver front-end - Ashwini (2018)
Satellite navigation systems (satnav) provides the specific location of an object in the spatial dimension. Although the satellite navigation systems were originally built for military application, it is now widely used for civilian purposes. Satnav finds many commercial applications in automobiles, consumer, agriculture, machine control and marine to name a few. However, its application in telecommunication has grown exponentially and cellphones are the wireless mode of telecommunication which uses satnav in the day – to – day activities such as pedestrian navigation, photography geocoding like Google Earth & Google Maps and location-based games & services. The satnav systems in telecommunication application are basically RF Receiver integrated circuits incorporated in cell phones, which receive radio frequency signal consisting of geospatial information from satellites. The objective of my master dissertation is an on-bench characterization of silicon RF Receiver Integrated Circuit and to verify its front-end design specifications. A detailed study and conceptual understanding are achieved in the process of characterizing the RF receiver IC developed for radio communication application. Contemplate the effective test set-up for on-bench characterization of RF receiver IC which consists of Low Noise Amplifier, RF Filter, Mixer, Programmable Gain Amplifier, IF Filter, PLL, ADC and other sub-blocks. The RFICs are tested across process corners (slow, typical and fast), across voltages (minimum, nominal and maximum) and for a range of temperature (cold, typical and hot). To validate RFIC a test program is developed in C# with visual studio for each of the RF parameter to be tested. Test measurement instruments are remotely controlled using standard commands for programmable instruments (SCPI). The test procedure involves automation in C# as well as MATLAB to analyze the test results. The test program automation involves remotely tuning the magnitude and phase of an input RF signal to the desired level by controlling signal generators and oscilloscope using SCPI commands and to generate FFT for the analysis of frequency spectrum. The thesis is concluded with the correlation of design simulation results and silicon validation results.